Genotypic characterization of cashew (Anacardium occidentale L.) clones using agro‐morphological traits. Issue 3 (2nd December 2020) - Adu‐Gyamfi, Paul K. K.; Akpertey, Abraham; Barnnor, Michael; Ofori, Atta; Padi, Francis
Abstract: High cropping efficiency implies that high yields are obtained from reasonably sized trees. We studied the general and specific combining ability (GCA and SCA) of selected cashew clones of Brazilian (A), Beninese (BE), and Ghanaian (SG) background for cropping efficiency and nut weight in the early years of bearing. Using North Carolina II mating design, four clones were crossed as males to three best clones recommended for farmers. The 12 F1 progenies were evaluated in the field at Wenchi (2012–2018) for increase in trunk cross‐sectional area at the vegetative (TCSAv) and reproductive (TCSAr) stages, canopy spread in the east‐west (CSew) and north‐south (CSns) directions, nut yield (NY), nut weight (NW), and cropping efficiency (CE) using a randomized complete block design with three replications. Cropping efficiencies were in the range of 30.8–67.4 g/cm 2 /year while nut weight and nut yield varied from 5.9 to 10.5 g/year and 477.8 to 939.4 kg ha ‐1  year ‐1 in the fourth to sixth years after planting, respectively. The Beninese progenies outperformed the Brazilian progenies for cropping efficiency. GCA effects were more important than SCA effects. Narrow‐sense heritability ranged from 0.47 (CE) to 0.80 (NW). Canopy spread in the north‐south direction correlated ( rg  = 0.98; p ≤  .001) strongly with cropping efficiency at the genotypic level. Among males, BE203 showed positive GCA effects for cropping efficiency, TCSAv, and nut yield, whereas A2 and SG273 showed positive GCA effects for nut weight. Among females, SG287 showed negative GCA effects for TCSAr. Our study provides evidence that, cashew tree size and nut quality are under genetic control and the identified clones represent a suitable genetic resource pool to increase productivity.